Character Education in Tarekat: A Phenomenological Study of Tarekat Syattariyah at Ki Bagus Rahsa Foundation Cirebon - Ahmad Yani; Siti Asiyah; Kariawan Kariawan (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Tarekat is one of the means of spiritual education that was built as a treasure of Islamic da'wah. Tarekat teaches various methods and spiritual education that can lead humans to recognize the Creator and have a good personality. This study aims to determine the teachings and values of character education applied at the Ki Bagus Rahsa Foundation to educate a person to become a perfect human being. The approach method uses descriptive phenomenological model, data collection through observation, interview, and documentation. this research is expected to be able to present objective and authentic field data. The result of the research found that the existence of Tarekat Syattariyah gives a spiritual contribution to its followers and the surrounding community in controlling bad behavior, suppressing negative actions, and overcoming social problems by relying on noble character education values (tata, discipline, honest, hard work, humble, polite, patient, resignation, wara', etc.). Starting from spiritual cleansing before the baiat procession, then baiat, to mujahadah which is routinely carried out alone or together at the Mursyid's house. By using applied tariqah, every jama'ah can become a person with physical and spiritual quality in this modern era.